2019
DOI: 10.1038/s41598-019-42252-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C@Ni-Al LDH HSS for efficient U-entrapment from seawater

Abstract: In this paper, a double hollow spherical shell composite modified with layered double hydroxide (C@Ni-Al LDH HSS) was fabricated for uranium(VI) (U(VI)) adsorption. Various batch experiments were carried out to investigate the influence of pH, concentration, time and coexistence ion on extraction. The results showed that the adsorption processes of U(VI) onto C@Ni-Al LDH HSS were spontaneous and endothermic and closely followed pseudo-second-order and Langmuir isotherm models. The equilibrium time and maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…4 a-c). According to IUPAC classification, the isotherm type IV was detected for ZnCr LDH, ZnCr LDH/CNT, and ZnCr LDH/BC, establishing the mesoporous nature of the synthesized materials [27] . Also, similar studies reported isotherm type IV for the ZnCr LDH [28] , [29] .…”
Section: Resultsmentioning
confidence: 97%
“…4 a-c). According to IUPAC classification, the isotherm type IV was detected for ZnCr LDH, ZnCr LDH/CNT, and ZnCr LDH/BC, establishing the mesoporous nature of the synthesized materials [27] . Also, similar studies reported isotherm type IV for the ZnCr LDH [28] , [29] .…”
Section: Resultsmentioning
confidence: 97%
“…3b, which were measured using 3 ppm U in pH 8.5 sodium carbonate solution and V m À1 up to 10 000, with the capacities of previously synthesised LDH materials, which have typically been measured under conditions irrelevant to seawater, namely pH 5-6 nitric acid and U concentrations 30-500 mg L À1 . [30][31][32]64 Under these conditions, U would be expected to be present as (UO 2 ) 2 (OH) 2 2+ and (UO 2 ) 3 (OH) 5 + . 34 These cationic hydroxide complexes cannot be expected to behave the same as the anionic carbonate complexes present in seawater.…”
Section: Materials Characterisationmentioning
confidence: 99%
“…To avoid the dissolution of LDH and the removal of metal ions that make up its crystal lattice into the filtrate, several authors have proposed a regeneration method using Na 2 CO 3 or NaHCO 3 solutions, which make it possible to remove intercalated forms of uranium from the interlayer space of LDH. The study [20] showed that at a Na 2 CO 3 concentration of 0.5 mol/L or more, the desorption efficiency is 80%. The authors [27] showed that after four cycles of adsorption-desorption with NaHCO 3 , the removal ratio of uranium by LDH was maintained at 90.27%.…”
Section: Introductionmentioning
confidence: 95%
“…To increase the sorption activity of LDH compared to analogues, a hydrothermal synthesis method is proposed, which includes the preliminary stages of obtaining carbon spheres and coating them with Ni-Al LDH [19]. In the article [20], a similar synthesis is implemented, where SiO 2 with AlOOH are used as microspheres. The study [21] proposed the preparation of three-dimensional hydroxyapatite materials based on Mg-Fe LDH (Mg-Fe-HAP) using ultrasonic synthesis, hydrothermal synthesis, and coprecipitation methods.…”
Section: Introductionmentioning
confidence: 99%